Frequency and Management of Adverse Drug Reactions Among Drug-Resistant Tuberculosis Patients: Analysis From a Prospective Study - Massud, Asif; Syed Sulaiman, Syed Azhar; Ahmad, Nafees; Shafqat, Muhammad; Chiau Ming, Long; Khan, Amer Hayat (Frontiers in Pharmacology, 2022)
Abstract Drug-resistant tuberculosis (DR-TB) management is often linked with a higher rate of adverse drug reactions (ADRs) needing effective and timely management of these ADRs, which if left untreated may result in a higher rate of loss to follow up of drug-resistant patients. Study objective: The study was aimed at prospectively identifying the nature, frequency, suspected drugs, and management approaches for ADRs along with risk factors of ADRs occurrence among DR-TB patients at Nishtar Medical University, Hospital, Multan, Pakistan. Materials and Methods: The prospective study included all the DR-TB patients enrolled for treatment from January 2016 to May 2017 at the study site. Patients were evaluated for the treatment induced ADRs as per standard criteria of the National Tuberculosis Program, Pakistan. Multivariate logistic regression was used to assess the independent variables associated with the occurrence of ADRs. Results: Out of 271 DR-TB patients included in the final analysis, it was observed that 55 patients (20.3%) experienced at least three ADRs. A total of 50 (18.5%) patients experienced zero adverse effects, while 15 (5.5%), 33 (12.2%), and 53 (19.6%) patients experienced one, two, and four ADRs, respectively. Gastrointestinal disturbances (66.7%), nervous system disorders (59.4%) and electrolyte disturbances (55.7%) remained the highest reported ADRs during therapy, followed by arthralgia (49.1%), ototoxicity (24%), pruritic reactions/rash (12.9%), dyspnoea (12.5%), and tinnitus (8.8%). Pulmonary cavitation at the baseline visit (p-value 0.001, OR 3.419; 95% CI (1.694 - 6.902) was significantly associated with the occurrence of ADRs among DR-TB patients. Conclusion: Frequency of ADRs was high among the study cohort, however, these were managed effectively. Patients with recognized risk factors for ADRs occurrence need continuous clinical management efforts.